Study of central venous catheter-related complications in major burn patients - Itisha Agrawal; Arun Bhatnagar (Wolters Kluwer Medknow Publications, 2022)
Background: Routinely changing central venous catheters (CVCs) as a prevention strategy of bbloodstreaminfections in burns patients has been controversial due to the paucity of evidence for appropriate timings of line changes. This study aims to ascertain the risk factors associated with central line-associated sepsis and thrombosis and to evaluate the role of heparin lock, routine line changes, and thromboprophylaxis in reducing the risk of complications associated with central venous catheterization. Materials and Methods: A retrospective observational hospital-based study on 50 patients admitted with major burns (involving 40% or more total body surface area [TBSA] in burn intensive care unit/ward at Gandhi Medical College and Associated Hamidia Hospital from May 2021 to June 2022. Nontunneled, triple-lumen central lines were inserted usingthe Seldinger technique preferentially on healthy skin and secured with Tegaderm™ CHG Chlorhexidine Gluconate transparent dressing. The removal of central lines was done sepsis (persistent rise of fever unresponsive to antipyretics or empirical antibiotics) or when distal limb swelling edema) developed. Routine removal of the central line was also done when resuscitation was over and parenteral nutritional supplementation was no longer needed (after 12-15 days) or before shifting from HDU or on discharge. Data collection included: Demographics, co-morbidities, type and cause of burn, %TBSA, route (subclavian, femoral, and jugular line), access (healthy/burned) of line, duration of line in situ, complications (cellulitis, edema, venous thrombosis, and persistent high-grade fever), culture/sensitivity (c/s) reports, duration of hospital stay, heparin prophylaxis, or treatment. The data were processed with Chi-square test. The primary outcome of this observational study was a measure of catheter-related bloodstream infections and symptomatic deep vein thrombosis and their correlation with demographics and various comorbidities. Result: Central line duration and age were identified as independent risk factors for central line-associated bloodstream infection (CLABSI), with central line duration the most significant predictor (P < 0.05). CLABSI occurred at 12.81 ± 2.967 days' postline insertion. Further research is needed to assess the role of routine line changes (every 12-15 days' postinsertion) in preventing CLABSI and heparin lock in reducing the incidence of venous thrombosis. Hospital stay was prolonged in the patients developing CVC-associated complications independently increasing morbidity in patients with severe burns, but was not found to be significant (P < 0.05). Conclusion: Jugular venous route should be preferred as the site of CVC insertion (easier and associated with a lower complication rate) and the duration of line kept in situ should be reduced. The blood c/s (preferably central line tip c/s) should be sent routinely after 10 days or on the first suspicion of complications to reduce the incidence and severity of CLABSI in major burn patients.